Presentism, Empire, and Nineteenth-Century Music - Brian C. Thompson (Musica Docta)
For many historians, and especially those in the USA, presentism has become one of the most contentious issues of the past twenty years. And what had at least been a civil debate has, in the heated intellectual/cultural climate of the past decade, turned particularly fractious, with historians now compelled to state publicly their position and carefully consider its possible impact on their careers. Following a hostile reaction to his August 2022 opinion piece “Is History History?”, University of Wisconsin professor and American Historical Association president James H. Sweet issued “a groveling apology” (in the words of New York Times columnist Bret Stephens) – in part due to concerns about the possible disruption of the Association’s forthcoming annual meeting. But what is the impact of presentism on music scholarship? Many of the concerns raised by Sweet, Stephens, and others appear as relevant to music as to history. As scholars and music historians, will the influence of presentism cause us to avoid topics that do not relate in positive ways to the dominant political concerns of the moment, or, at least deter us from asking questions that might lead to difficult conclusions? In this essay, I explore some of these questions with reference to an ongoing project which focuses on the De Angelis family, Sicilian musicians and educators who found their way to North America in the mid-nineteenth century by way of the British Army.